Comparison of performance, incidence of foot pad dermatitis, and gut microflora of broiler chickens raised on floor pens and in cages in a tropical environment - M. S., Zulfahmi; N. N., Syafiqa; Idrus, Zulkifli; Mohamed, Elmutaz Atta Awad; Farjam, Abdoreza Soleimani (Faculty of Animal Husbandry, Brawijaya University, 2017)
This study was conducted to determine the effects of cage and floor pen rearing systems on growth performance, incidence of footpad dermatitis (FPD), and cecal E. coli population in broiler chickens in a tropical environment. A total of 200 day-old male broiler chicks (Cobb 500) were equally allocated to either battery cages with wire floors (CG) or floor pens with wood shavings as litter (FP) from day 1 to 42. The body weight and feed intake of CG broilers were significantly lower than those on floor pens. However, the CG broilers had significantly better feed conversion ratios than their FP counterparts. The incidence of FPD and cecal E.coli population were higher in FP birds than those of the CG group which suggest poorer welfare in the former.